The Economic Opennes and its Influence on the Level of Corruption in the Czech Republic - Knězáčková Radka; Linhartová Veronika (Vysoká škola báňská-Technická univerzita Ostrava, 2013)
The international migration is one of the aspects of the globalization process. Strong migration tendencies can be found out in the Czech Republic. The country used to be a transit country, it was used for entry into the Western European countries, but over time it has become destination for permanent residence of foreigners. During last twenty years the number of foreigners increased thirteen times in the Czech Republic and the immigration is one of the fastest in the world. Habits of foreign countries are coming in the Czech Republic together with people. So after opening of the borders in 1989 the Czech Republic became the place where new people came. New traditions, behaviour, habits and customs were coming together with people and firms. Unfortunately it has not only positive effects but also negative effects. For example corrupt practises are transmitted from countries with higher level of corruption to countries with lower level of corruption. It means worse ratings of the corruption indicators for the Czech Republic. Worse evaluation of the country determinates decline of attraction of the country for potential foreign investors.The evaluation of influence of economic openness on corruption in the country is the aim of this paper. Simultaneously dependence between the level of corruption in the country and the arrival of foreign companies and their workers will be verified.
Vliv stupně otevřenosti ekonomiky na míru korupce v České republice
Keywords: Bribe Payers Index; corruption; Corruption Perception Index; migration; openness of economy; index plátců úplatků; index vnímání korupce; korupce; migrace; otevřenost ekonomiky